The influence of electronic word of mouth in internet mediated social websites on consumer's purchase intention in hospitality industry - Shamsuddin, Nur Suryanttie (2015)
Internet and technology have transformed Word of Mouth (WOM) into eWOM which its impact may be different from traditional WOM. Since Internet gets people connected, the eWOM is distributed to a vast audience at an extraordinary speed. In addition, with the increase use of social website (ie. Facebook) , the consumers has tendency to share their feelings, knowledge and experiences within this social network. Thus, eWOM can reach to a huge number of consumers. For the study, Facebook is used as a research platform. There are possibilities of eWOM to influence purchase intention due to its large number of active users while the self-peceived knowledge can influence the decision-making process. Hospitality industry from the context of Malaysia was selected for this study. So, consumers with knowledge of this industry might have more control in their decision making rather to depend on the eWOM in their decision making process. For the study, the eWOM dimensions are applied to determine the purchase intention of consumers in the hospitality industry. The proposed research framework includes six dimensions namely obtain-buying related information, learn to consume a product or services, social orientation,perceived usefulness, perceived benefit, and trust, and mediated variables as perceived knowledge and finally purchase intention. Data indicated that most of the respondents were female; the age mean is 29.80 years old with majority monthly income between RM2001 to RM3000. Majority, they agree that eWOM help them to thoughout their decision making process thus induce the purchase intention even some of them are not sure either they have the self-perceived knowledge or they don’t. Trust was identified to be the main dimensions that have strong significant relationship with purchase intention. The other dimensions such as learn to consume product or services and perceived benefit are found to have a significant contribution towards the purchase intention scores. Using hierarchical multiple regression analysis, self-perceived knowledge was found to be significant as it partially mediate the relationship between eWOM and the consumer’s purchase intention. The results derived from this study showed that there is a significant relationship between eWOM’s dimensions and purchase intention. Web designers and marketers can benefit from this data by understanding the behavior of the consumers as they interact between each other. They can use this as an opportunity and to be aware of any possible threat.